The Budget of Macrobenthic Reworked Organic Carbon: A Modeling Case Study of the North Sea. Issue 6 (17th June 2019) - Zhang, Wenyan; Wirtz, Kai; Daewel, Ute; Wrede, Alexa; Kröncke, Ingrid; Kuhn, Gerhard; Neumann, Andreas; Meyer, Julia; Ma, Mengyao; Schrum, Corinna
Abstract: The importance of macrobenthos in benthic‐pelagic coupling and early diagenesis of organic carbon has long been recognized but has not been quantified at a regional scale. By using the southern North Sea as an exemplary area we present a modeling attempt to quantify the budget of total organic carbon (TOC) reworked by macrobenthos in seafloor surface sediments. Vertical profiles in sediments collected in the field indicate a significant but nonlinear correlation between TOC and macrobenthic biomass. A mechanistic model is used to resolve the bidirectional interaction between TOC and macrobenthos. A novelty of this model is that bioturbation is resolved dynamically depending on variations in local food resource and macrobenthic biomass. The model is coupled to 3‐D hydrodynamic‐biogeochemical simulations to hindcast the mutual dependence between sedimentary TOC and macrobenthos from 1948 to 2015. Agreement with field data reveals a satisfactory model performance. Our simulations show that the preservation of TOC in the North Sea sediments is determined not only by pelagic conditions (hydrodynamic regime and primary production) but also by the vertical distribution of TOC, bioturbation intensity, and the vertical positioning of macrobenthos. Macrobenthos annually ingest 20–35% and in addition vertically diffuse 11–22% of the total budget of TOC in the uppermost 30‐cm sediments in the southern North Sea. This result indicates a central role of benthic animals in modulating the organic carbon cycling at the sediment‐water interface of continental margins. Key Points: A mechanistic model quantifies the cycling of organic carbon modulated by macrobenthos Bioturbation stabilizes sedimentary organic carbon budget by changing degradation efficiency Macrobenthos may annually rework more than 50% of TOC in surface sediments at a regional scale